Report of the third Meeting of Regional [Fishery] Body Secretariats Network : Rome, 7-8 February 2011. - Meeting of Regional Fishery Body Secretariats Network 2011 : Rome, Italy); Food and Agriculture Organization of the United Nations (Rome : Food and Agriculture Organization of the United Nations, 2011)
The Third Meeting of Regional Fishery Body Secretariats Network (RSN-3) was held in Rome, Italy, from 7 to 8 February 2011. It addressed many pressing issues relating to global and regional fisheries governance, including illegal, unreported and unregulated (IUU) fishing, overcapacity, the ecosystem approach to fisheries management, small-scale and inland fisheries and the outcomes of the twenty-ninth Session of FAO Committee on Fisheries (COFI) held in Rome during the previous week. Twenty-eight Regional Fishery Body (RFB) Secretariats were represented at the meeting with varying responsibilities over inland, coastal and marine fisheries and aquaculture, as well as four intergovernmental organizations. The meeting reached a number of conclusions regarding matters that merit the attention of RFBs, governments and FAO. The RSN also issued a Statement responding to unsubstantiated information that had been published about RFBs and elaborating the challenges and achievements of RFBs.
"FIPI/R980 (En)."
Also available on the World Wide Web.
Keywords: Fishery management -- Congresses; Fisheries -- Congresses